Correlation between body constitution and quality of life in hypertensive elderly in the Berbah health center area - Putri, Yunita Andhini; Nurjannah, Intansari; Harjanto, Dwi (International Journal of Research in Medical Sciences, 2023)
Background: One of the health conditions that the majority of the elderly experience is hypertension. Those who cannot adjust to changes in their physical condition and health decline will experience a deterioration of their quality of life. The elderly’s health conditions can be examined using traditional Chinese medicine constitution which is used for disease prevention, treatment, and health improvement. This research aimed to investigate the correlation between body constitution and quality of life in hypertensive elderly patients in Sendangtirto Village. Methods: This research employed a quantitative approach with an analytic research type and cross-sectional design. The respondents of this research were 79 elderlies with hypertension in Sendangtirto Village, obtained by simple-random sampling technique. This research was started from February to March 2023. The instruments used were the traditional Chinese medicine constitution (TCMC) and the WHOQoL-BREF instruments. The analytical test employed was Kendall’s tau correlation to investigate the correlation between the two examined variables. Results: This research shows that 64.5% (51 respondents) can be categorized into sick category and 35.44% (28 respondents) are in non-sick category. As many as 87.34% (69 respondents) were in moderate quality of life and 12.66% (10 respondents) are in high quality of life. The final result of body constitution and the final result of quality of life did not have a significant correlation (p=0.306; r=0.116). Conclusions: Body constitution and quality of life do not have a significant correlation in hypertensive elderly in Sendangtirto village.